Lesson Study Pembelajaran Berdiferensiasi Untuk Meningkatkan Literasi Sains Komunitas Belajar Guru IPA di Kota Lubuklinggau - Yaspin Yolanda; Andriana Sofiarini; Aulia Faizah Putri Vinsa (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This differentiated learning lesson study for the Lubuklinggau City Science Teacher Learning Community was carried out at Lubuklinggau City 5 Public High School on January 10-12, 2024 involving 20 science teachers at Lubuklinggau City 5 Public High School. This activity uses the Plan, Do, See and Redesign cycle. To measure participants' achievement using a pre-test and post-test before the activity. The Plan stage begins with identifying learning problems which include teaching materials, learning strategies, and who will act as a model teacher; The Do (implementation) stage, namely: (a) learning implementation activities carried out by one of the model teachers to put into practice the learning plans that have been prepared together, and (b) observation activities carried out by the teacher, the principal acting as an observer. In the See (reflection) stage, due to efforts to improve the learning process, lecturers and teachers then reflect on what is interesting, what things need to be improved and what things we need to leave behind. The results of the analysis show that differentiated learning lesson study is very useful in increasing scientific literacy. Lesson study has a positive impact on teachers collaborating and sharing good practices in scientific literacy teaching strategies so that they can improve the quality of learning and increase teacher pedagogical competence. Lesson study can develop skills in problem solving.